2017
DOI: 10.1002/jcad.12112
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Intervention Training for K–12 Schools: A Quasi‐Experimental Study on ASIST

Abstract: This quasi‐experimental study investigated differences between 104 school personnel who received a standardized suicide awareness and prevention training (i.e., Applied Suicide Intervention Skills Training) and 45 control group participants. Pre‐ and posttraining data included experimental and control group participants' (a) suicide intervention skills; (b) attitudes toward suicide; (c) knowledge of suicide; and (d) comfort, competence, and confidence in responding to individuals at risk of suicide. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
6
30
0
1
Order By: Relevance
“…This was the approach adopted by the Farm‐Link project, which aimed to improve the mental well‐being of people living and working on farms in New South Wales (NSW) . The usefulness of a brief education program compared to more intensive programs like Mental Health First Aid, or Applied Suicide Intervention Skills, has been highlighted by previous research …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was the approach adopted by the Farm‐Link project, which aimed to improve the mental well‐being of people living and working on farms in New South Wales (NSW) . The usefulness of a brief education program compared to more intensive programs like Mental Health First Aid, or Applied Suicide Intervention Skills, has been highlighted by previous research …”
mentioning
confidence: 99%
“…5,[16][17][18]20 This was the approach adopted by the Farm-Link project, which aimed to improve the mental well-being of people living and working on farms in New South Wales (NSW). 16 The usefulness of a brief education program compared to more intensive programs like Mental Health First Aid, 21,22 or Applied Suicide Intervention Skills, 23 has been highlighted by previous research. 24 The aim of the current research was to analyze the effectiveness of the SCARF (Suspect, Connect, Ask, Refer, Follow-Up) brief education workshop in improving suicide literacy, reducing stigmatizing attitudes, enhancing mental well-being, and increasing confidence to assist people at risk of suicide.…”
mentioning
confidence: 99%
“…Although these constructs are commonly discussed in the SI literature, there is no consensus on how to assess them. ORS did not report internal consistencies but did publish specific item phrasing, which has permitted repeatable means of assessing these constructs (Shannonhouse, Lin, Shaw, & Porter, 2017; Shannonhouse, Lin, Shaw, Wanna, & Porter, 2017). In the present study, we assessed attitudes about suicide through five items (e.g., “Is suicide preventable?” “Should you directly ask about suicide?”); internal consistency was low to adequate at pre‐ (α = .63) and posttest (α = .81), and the control group test–retest reliability estimate was rather low ( r = .57, p < .01).…”
Section: Methodsmentioning
confidence: 99%
“…Although this scoring approach was an improvement over the original ceiling‐limited SIRI, which asked participants to choose the better of two responses (Neimeyer & Bonnelle, 1997), there appears to be a new scoring limitation. In studies of K–12 school staff (Shannonhouse, Lin, Shaw, & Porter, 2017) and university employees (Shannonhouse, Lin, Shaw, Wanna, & Porter, 2017), some participants scored worse on the SIRI‐2 after ASIST training. Item‐level analysis showed that the participants “overestimated the helpfulness or harmfulness of responses at posttest, becoming more discrepant from the average expert scores” (Shannonhouse, Lin, Shaw, & Porter, 2017, p. 11).…”
Section: Methodsmentioning
confidence: 99%
“…Six articles featured qualitative and quantitative evaluation of workshops, interventions, or course experiences offered to student or professional audiences. Features include strong quantitative evidence of effectiveness of the applied suicide intervention skills training model with practicing school personnel (Shannonhouse, Lin, Shaw, & Porter, 2017) and preliminary quantitative evidence supporting STORM suicide gatekeeper training in the United Kingdom (Gask, Coupe, McElvenny, & Green, 2017). Several researchers found mixed‐methods evidence to support effectiveness of a responsive training intervention focused on needs of LGBT clients or students (Luke & Goodrich, 2017; Rivers & Swank, 2017).…”
Section: Teaching and Trainingmentioning
confidence: 99%